2005
DOI: 10.1074/jbc.m414390200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Inflammatory Response in Neural Cells in Vitro by Thiadiazolidinones Derivatives through Peroxisome Proliferator-activated Receptor γ Activation

Abstract: In most neurodegenerative disorders, including multiple sclerosis, Parkinson disease, and Alzheimer disease, a massive neuronal cell death occurs as a consequence of an uncontrolled inflammatory response, where activated astrocytes and microglia and their cytotoxic agents play a crucial pathological role. Current treatments for these diseases are not effective. In the present study we investigate the effect of thiadiazolidinone derivatives, which have been recently suggested to play a role in neurodegenerative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
136
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 178 publications
(140 citation statements)
references
References 46 publications
3
136
0
Order By: Relevance
“…Both types of activated glia express PPARγ in cultures and in injured brain (9). In addition, thiazolidinedione derivatives, including pioglitazone, were reported to inhibit induction of inflammatory mediators in lipopolysaccharide-stimulated astrocyte cultures and microglia cultures (10). We therefore, propose a hypothesis that pioglitazone may control neuropathic pain through activation of PPARγ in glial cells activated at different phases.…”
Section: Discussionmentioning
confidence: 99%
“…Both types of activated glia express PPARγ in cultures and in injured brain (9). In addition, thiazolidinedione derivatives, including pioglitazone, were reported to inhibit induction of inflammatory mediators in lipopolysaccharide-stimulated astrocyte cultures and microglia cultures (10). We therefore, propose a hypothesis that pioglitazone may control neuropathic pain through activation of PPARγ in glial cells activated at different phases.…”
Section: Discussionmentioning
confidence: 99%
“…Later, other more detailed studies have demonstrated that PPARγ presents a high degree of expression in the rat cerebral frontal cortex, in all layers and mainly in the neurons of layer II, showing immunostaining in the nuclear and cytoplasmic compartments (44). Also, PPARγ expression has been detected in microglial cells and in astrocytes, making these cells potential targets for the PPARγ ligand anti-inflammatory activity in neurological diseases having an associated inflammatory component (45).…”
Section: A Cox-2-dependent Mechanism Of Inflammatory Balance: Deoxy-pmentioning
confidence: 99%
“…At the end of the treatment period cultures, grown on glass coverslips in 24-well cell culture plates, were washed with phosphate-buffered-saline (PBS) and processed for immunocytochemistry as previously described (Luna-Medina et al, 2005). Briefly, cells were fixed for 30 minutes with 4% paraformaldehyde at 25°C, and permeabilized with 0.5% Triton X-100 for 30 minutes at 37°C.…”
Section: Immunocytochemistrymentioning
confidence: 99%
“…Rat primary astrocyte and microglial cultures were prepared as previously described (Luna-Medina et al, 2005). Mouse primary C/EBPβ +/+ and C/EBPβ -/-astrocyte and microglial cultures were prepared as rat primary cells with some minor modifications.…”
Section: Primary Cell Culture and Treatmentmentioning
confidence: 99%